2022
DOI: 10.3389/fpsyg.2022.745158
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Post-traumatic Stress Disorder Among Nurses During COVID-19

Abstract: ObjectiveTo investigate post-traumatic stress disorder (PTSD), perceived professional benefits and post-traumatic growth (PTG) status among Chinese nurses in the context of the COVID-19 pandemic and to compare the differences between nurses working inside and outside Hubei.MethodsFrom February 18 to February 25, 2020, the authors constructed the questionnaire using the Questionnaire Star platform, and convenience sampling was used to distribute the questionnaire via WeChat. Nurses who worked at the hospital du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…The pandemic has been a major stressor for nurses working at pandemic clinics in Istanbul because Istanbul has had the most COVID-19 cases since the onset of the pandemic. Similarly, Jiang et al (2022) found statistically significant higher PTG scores in nurses working in Hubei than in nurses working outside Hubei, despite both groups were exposed to COVID-19 (Jiang et al, 2022).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The pandemic has been a major stressor for nurses working at pandemic clinics in Istanbul because Istanbul has had the most COVID-19 cases since the onset of the pandemic. Similarly, Jiang et al (2022) found statistically significant higher PTG scores in nurses working in Hubei than in nurses working outside Hubei, despite both groups were exposed to COVID-19 (Jiang et al, 2022).…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, Jiang et al. (2022) found statistically significant higher PTG scores in nurses working in Hubei than in nurses working outside Hubei, despite both groups were exposed to COVID‐19 (Jiang et al., 2022).…”
Section: Discussionmentioning
confidence: 91%
“…PTSD is a serious but treatable mental disorder that occurs after a life-threatening traumatic event, and people show symptoms of traumatic reexperience, hypervigilance, avoidance, and numbness, which usually occur 3 months to several years after the trauma ( 21 , 22 ). In terms of gender, women are more susceptible, such as pregnant women ( 23 ) and nurses ( 24 ). A 3-month follow-up record of COVID-19 survivors shows that previous psychiatric diagnosis and obesity were risk factors for developing PTSD ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Em relação ao estado civil dos enfermeiros que atuaram na COVID-19, uma pesquisa realizada na China, com 3,149 profissionais, relatou que 73,4 % eram casados e que a COVID-19 pode causar transtornos como o TEPT devido à angústia causada pelo isolamento social e à incerteza de uma doença que pode afetar seus familiares 13 .…”
Section: /14unclassified